Impact of Baseline Hypoalbuminemia on Long-Term Survival Following Acute Myocardial Infarction According to Body Mass Index - Alon Shechter; Shani Dahan; Arthur Shiyovich; Harel Gilutz; Ygal Plakht (Journal of Cardiovascular Development and Disease)
Serum albumin and body mass index (BMI, kg/m2) have been associated with outcomes following acute myocardial infarction (AMI). Aiming to assess whether the mortality risk inflicted by hypoalbuminemia (<3.5 g/dL) in this context is influenced by BMI, we conducted a retrospective analysis of AMI survivors hospitalized during 2004–2017. Stratified by admission-time albumin level and BMI, eligible cases were evaluated for all-cause mortality up to 10 years after discharge. A total of 6283 individuals (74.1% males, mean age 64.1 ± 13.1 years, 44.3% with ST-elevation MI) were included. Of them, 22.7% had hypoalbuminemia and 1.2%, 41.0%, and 28.6% were underweight (BMI < 18.5), overweight (BMI 25–30), and obese (BMI ≥ 30), respectively. Over a median of 7.9 (IQR, 4.8–10.0) years of follow-up, 42.5% of patients died. Hypoalbuminemia was independently associated with a heightened mortality risk overall (AdjHR = 1.54, 95%CI 1.42–1.67, p < 0.001), accounted for by the normal weight (AdjHR = 1.73, 95%CI 1.50–1.99, p < 0.001), overweight (AdjHR = 1.55, 95%CI 1.35–1.79, p < 0.001), and class 1 obesity (BMI 30–35) (AdjHR = 1.37, 95%CI 1.12–1.68, p = 0.002) subgroups. Upon interaction analysis, the mortality risk imposed by hypoalbuminemia was most pronounced among individuals with normal BMI. In conclusion, hypoalbuminemia constituted a negative prognostic marker for long-term survival in AMI patients with normal or mildly elevated but not reduced or severely increased BMI. Pending further research, addressing hypoalbuminemia based on BMI range may prove beneficial.